2002
DOI: 10.1161/01.atv.0000015078.09208.92
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nuclear Factor-κB Activation in Metalloproteinase-1, -3, and -9 Secretion by Human Macrophages In Vitro and Rabbit Foam Cells Produced In Vivo

Abstract: Abstract-Metalloproteinase secretion by macrophages is believed to play a key role in the matrix degradation that underlies atherosclerotic plaque instability and aneurysm formation. We studied the hypothesis that nuclear factor-B (NF-B), a transcription factor, is necessary for metalloproteinase secretion and, hence, is a target for pharmacological intervention. Key Words: macrophages Ⅲ foam cells Ⅲ metalloproteinases Ⅲ nuclear factor-B R upture of the fibrous cap of the atherosclerotic plaque is a key event … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
127
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(143 citation statements)
references
References 41 publications
14
127
1
1
Order By: Relevance
“…17 In this report, we have made similar observations on MMP-3 induction in the T98G cells upon TNFa treatment. Additionally, our results showed that IFNg blocks the binding of Ets-1 and NFjB to their respective enhancer sequences, which are present in the MMP-3 promoter.…”
Section: Discussionsupporting
confidence: 76%
“…17 In this report, we have made similar observations on MMP-3 induction in the T98G cells upon TNFa treatment. Additionally, our results showed that IFNg blocks the binding of Ets-1 and NFjB to their respective enhancer sequences, which are present in the MMP-3 promoter.…”
Section: Discussionsupporting
confidence: 76%
“…tion and formation of cerebral aneurysms in rat aneurysmal models. 4 Nuclear factor-kB also regulates the transcription of some proinflammatory genes such as iNOS 36 and matrix metalloproteinases (MMPs), 9 which are of functional importance for the progression of cerebral aneurysms. Recent reports have shown that regression of some inflammatoryrelated molecules have protective effects in experimental cerebral aneurysm models.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…The expression of the AP-1 transcription factor complex is positively associated with matrix metalloproteinase expression, 94,95 and cigarette smoke is associated with increased expression of AP-1. 96,97 Secretion of MMP-1 and MMP-3 from macrophages stimulated in vitro or in vivo depends on the activation of NF-B, 98 and NF-B is required for cytokine upregulation of MMP-1, MMP-3, and MMP-9 in VSMCs. 99 Cigarette smoke itself is associated with activation of NF-B.…”
Section: Smoking and Regulation Of Matrix Metalloproteinase Activitymentioning
confidence: 99%